Securing Data in Cloud- A Physical Cyber System - Reddy, K. Pandu Ranga; Reddy, Dr. K. Thammi (IJRDO -Journal of Computer Science Engineering, 2017)
Today’s networked world, huge amount of data that is being generated by various physical devices for communication. It is due to sudden surge in the use of IoT devices in various sectors like health monitoring, automobile industry, home appliances etc. These data objects are stored in cloud which consists of sensitive data objects along with other information. Cloud storage is a physical cyber system which attracts users from all sectors to store their data in it. Data storing in the cloud is useful to the individual/organizations to save their maintenance cost. Sharing those stored data through cloud makes the organization to improve their business. Though it increases the business it also increases security challenges. Lot of researches has done to provide secure data sharing through cloud storage. Still more mechanisms are requires to fulfill the requirements of secure data sharing. . The possible attacks at cloud storage are Known-ciphertext, Known-Plaintext and Guessing-keyword. Techniques for secure data sharing through cloud Searchable Symmetric encryption (SSE).Public Key Encryption with Keyword Search (PEKS), Attribute Based Encryption (ABE). Earlier research focus on user attributes for secure data sharing. But, organizations point of view they will have levels of priority to get access of the data. The proposed framework to encrypt the data based on user priority levels before outsourcing the data and allocates credentials based on priority level hierarchy. The data sharing architecture should able to support user attribute revocation as well as the priorities revocation. It should able to provide verifiability regarding accuracy of cloud service provider’s search on behalf of data user. In the proposed architecture the index format includes encrypted keyword which is constructed with access policies and time. The user priorities are considered along with attributes